Laser Effect on Fatique Resistance of Carbon Steel (Baghdad Science Journal, 2025)
Laser beam has been widely used to improve the mechanical properties of the metals. It used for cutting, drilling, hardening, welding……etc. The use of Laser beam has many features in accuracy and speeding in work, also in the treatment of metals locally, and in the places that is hard to reach by traditional ways.In this research a surface treatment was done to medium carbon steel (0.4%C) which is common kind of steel that is used in industry. Pulsing Neodymium -YAG Laser has been used and 1.06 micrometer wave length and 5 msec and the distance is about 30 centimeter between the exit area of the Laser beam from the system and the piece that treated . We are going to check the fatigue resistance for samples that is treated by Laser beam and Scanning Electron Microscope (SEM) and also we made check for the microstructure by using the light microscope and the SEM for the breaking samples. The results of checking showed that there is an improvement in the fatigue resistance after the treatment by the Laser beam. The results of microscope checking showed that the beginning of the failure is from the surface area and there is more than one level of the break.